PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN KINERJA TERHADAP NILAI PERUSAHAAN DENGAN TIPE INDUSTRI SEBAGAI VARIABEL MODERASI - Henik Haris Astuti; Roni Aron Oktavianus; Yvonne Augustine (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
This study aims to examine and analyze the influence of sustainability report disclosure, financial performance, non-financial performance on firm value with industry type as a moderating variable. The sample used in this study are companies that listed on the Indonesia Stock Exchange (IDX) and publish sustainability report for the period 2012-2016. Testing was done by using multiple regression analysis with moderation regression analysis method. The result of this research are: (1) corporate social responsibility disclosure has an positif effect on firm value, (2) financial performance has an positif effect to firm value, (3) non financial performance has no effect on firm value, (4) industry type not moderating the influence of corporate social responsibility disclosure on firm value (5) industry type not moderating the influence of financial performance on firm value, and (6) industry type not moderating the influence of non financial performance on firm value.